Pengaruh Return On Assets (ROA) Dan Arus Kas Operasi Terhadap Kondisi Financial Distress Pada Perusahaan Jasa Sub Sektor Transportasi & Logistic Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Deviana Sofyan; Elmi Yadi; Sepniati Anak Ampun (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study is to examine the relationship between financial distress and returns on assets, operating cash flow, and the combination of the two in service companies listed on the Indonesia Stock Exchange that fall under the Transportation & Logistics subsector from 2020 to 2022. Between 2020 and 2022, 34 stocks belonging to transportation and logistics service providers listed on the Indonesia Stock Exchange made up the study's population. To conduct this research, a purposive sampling strategy was employed to choose a sample of 28 service providers from the transportation and logistics subsector. Methods used in this research include descriptive statistics, multiple linear regression analysis, and classical assumption tests; data gathering approaches include documentation. The study employs a descriptive quantitative approach. Using a t-test to test hypotheses, we found that operating cash flow significantly impacted financial distress in transportation and logistics service companies listed on the Indonesia Stock Exchange from 2020 to 2022, but returns on assets had no significant effect. Companies listed on the Indonesia Stock Exchange in the transportation and logistics subsector from 2020 to 2022 had less financial difficulty when ROA and operational cash flow improved together, according to the F test. The determination coefficient (R2) test showed that returns on assets and operational cash flow accounted for 44.1% of the financial distress variable, while other factors, which were not assessed in this research, accounted for the remaining 55.9%.